One Health Approach to Leptospirosis: Dogs as Environmental Sentinels for Identification and Monitoring of Human Risk Areas in Southern Brazil - Sohn-Hausner, Natacha; Kmetiuk, Louise Bach; da Silva, Evelyn Cristine [UNESP]; Langoni, Helio [UNESP]; Biondo, Alexander Welker (MDPI, 2023)
Leptospirosis has been a neglected, widespread and reemerging zoonotic disease of global importance. The One Health holistic approach combining human, animal and environmental health has been important for control and prevention of zoonotic disease. An urban municipality in Southern Brazil with a high prevalence of leptospirosis was selected by convenience, with asymptomatic human and canine individuals serologically tested using MAT against 30 Leptospira spp. serovars. Epidemiological questionnaires were assessed along with the historical national database, with associated risk factors to dog and human seropositivity analyzed using multiple logistic regression. The spatial distribution of retrospective human leptospirosis cases was analyzed using a Kernel map and overlapped dog seropositivity and historical flooding areas, demonstrating that domestic and asymptomatic dogs may be important environmental sentinels for leptospirosis in such urban areas, even in the absence of human seropositivity and low canine seropositivity. Associated risk factors for leptospirosis in dogs and humans according to multiple regression included healthy dogs (p = 0.02, odds ratio—OR = 0.17, confidence interval of 95%CI 0.03–0.71) with indoor access (p = 0.059, OR = 5.12, 95%CI 1.10–37.7) and human males (p = 0.042, OR = 2.44, 95%CI 1.08–6.11) with presenting calf pain (p = 0.005, OR = 3.14, 95%CI 1.46–7. 14), jaundice (p < 0.001, OR = 4.61, 95%CI 2.11–10.10) and renal failure (p = 0.008, OR = 4.49, 95%CI 1.49–13.76). The greater the rain precipitation (above 3 mm of average annual precipitation), the higher the number of leptospirosis cases in humans. In conclusion, dog active serosurvey and rain precipitation should be systematically reported and plotted altogether as a basis for the early detection and monitoring of human risk areas. Such findings may serve as a basis for public health policies in Brazil and other endemic countries worldwide.
Keywords: health policy; risk mapping; sentinel dog; vulnerability; vulnerable populations; zoonoses